Firing Pattern Formation by Transient Calcium Current in Model Motoneuron - Svirskienė, N.; Svirskis, G. (Nonlinear Analysis: Modelling and Control, 2000)
Firing properties of neurons are important in signal detection and generation in nervous system. Spinal cord motoneurons have membrane properties adapted to muscle properties. In this work we explored the relation between the first interspike interval and the amplitude of injected current. It was shown that increased sensitivity of firing frequency to the injected current at higher firing frequencies is due to the transient calcium current. Particularly, the specific density of N-type channels and the speed of their deactivation define the steepness and onset of the second range in frequency versus current relation.
Keywords: neural system; motoneuron; action potential; calcium channel; modeling